Pengaruh Baby Spa Dan Pijat Bayi Terhadap Kualitas Tidur Bayi Usia 0-6 Bulan Di Klinik Dira Baby Spa Kabupaten Bangka : The Effect of Baby Spa and Baby Massage on Sleep Quality of Babies Aged 0-6 Months at the Dira Baby Spa Clinic, Bangka Regency - Pramita, Lara (Dohara POAJ, 2025)
Introduction: Poor sleep quality can lead to several disturbances. In infants, it can cause a decline in daily activities, feelings of fatigue, weakness, more labile emotions, anxiety, fussiness, inability to concentrate, and excessive drowsiness. The importance of sleep for infant development necessitates that their sleep needs be fully met to avoid negative impacts on their development. This research aims to determine the effect of baby spa and infant massage on the sleep quality of infants aged 0-6 months at Dira Baby Spa Clinic, Bangka Regency, in 2024. Methods: The research method used is a literature review case study. This study was conducted at Dira Baby Spa Clinic in December 2024. Results: The results of the study consist of infants aged 0-6 months. The sample size needed for this study is 2 infants experiencing sleep quality issues. Discussion: The results were respondents who received baby massage intervention experienced an increase in sleep duration of 2-3 hours from 8 hours to 10-11 hours. Meanwhile, respondents who received baby spa intervention experienced an increase in sleep duration of 3-4 hours from 8 hours to 11-12 hours.